Polylactic acid resin composition

The polylactic acid resin composition with a high filler content, aided by a filler dispersant and/or dispersion polymer, addresses the challenges of filler dispersibility and molding cycle times, resulting in enhanced mechanical and thermal properties and improved productivity.

JP7658741B2Active Publication Date: 2025-04-08NAGASE & CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020214460
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-04-08
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Conventional polylactic acid resin compositions face challenges in achieving high filler content due to production issues, such as filler dispersibility and uniformity, which limits the demonstration of filler properties like rigidity and heat resistance, and results in long molding cycles.

Method used

A polylactic acid resin composition that includes a polylactic acid resin, a filler, a filler dispersant, and/or a filler dispersion polymer, with a filler content of 30% to 70% by weight, which improves filler dispersibility and allows for higher filler content, thereby enhancing mechanical and thermal properties while reducing molding cycle times.

Benefits of technology

The composition achieves excellent mechanical properties, including high flexural modulus and heat resistance, along with improved productivity during molding and enhanced filler dispersibility, making it suitable for various industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658741000001
    Figure 0007658741000001
  • Figure 0007658741000002
    Figure 0007658741000002
  • Figure 0007658741000003
    Figure 0007658741000003
Patent Text Reader

Abstract

To provide a resin composition that has excellent properties attributable to a filler, the resin composition offering high productivity during its molding, and a method for producing the same.SOLUTION: The inventive polylactic resin composition contains a polylactic acid resin and a filler, the polylactic acid resin further containing a filler dispersant and / or a polymer for filler dispersion. In the polylactic resin composition, the content of the filler is 30 wt.%-70 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polylactic acid resin composition. [Background technology]

[0002] Polylactic acid is a plant-derived resin and is known as a biodegradable resin. Polylactic acid is sometimes crystallized before use to improve heat resistance, but the crystallization rate of polylactic acid is slow, resulting in problems such as low productivity during molding, such as a long molding cycle during injection molding.

[0003] In addition, attempts have been made to obtain molded articles with improved properties by blending various fillers into resin compositions. Blending fillers at high concentrations is very difficult due to production problems (e.g., feed necks when feeding fillers into a kneader), filler dispersibility problems, etc. For example, Patent Document 1 discloses blending polylactic acid with a filler to obtain a resin composition, but even in this document, the amount of filler blended is practically limited to about 30% by weight. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2004-352844 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, in conventional resin compositions in which it is difficult to contain a high concentration of filler, there is a problem that the properties attributable to the filler (for example, rigidity, heat resistance, shape stability) are not fully exhibited. The present invention has been made to solve this problem, and an object of the present invention is to provide a resin composition that is excellent in the properties attributable to the filler and has excellent productivity during molding, and a method for producing the same. [Means for solving the problem]

[0006] The polylactic acid resin composition of the present invention is a polylactic acid resin composition comprising a polylactic acid resin and a filler, the polylactic acid resin composition further comprising a filler dispersant and / or a filler dispersion polymer, and the content of the filler in the polylactic acid resin composition is 30% by weight to 70% by weight. In one embodiment, the filler dispersing agent is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, fatty acid amides, polyglycerin fatty acid esters, condensed hydroxy fatty acids, and alcohol esters of condensed hydroxy fatty acids. In one embodiment, the filler dispersion polymer is at least one selected from the group consisting of polyethylene-based resins, polypropylene-based resins, polyvinyl alcohol-based resins, polystyrene-based resins, polyacrylate-based resins, polymethacrylate-based resins, and water-soluble polysaccharides. In one embodiment, the filler dispersion polymer is a polyvinyl alcohol resin. In one embodiment, the total content of the filler dispersant and the filler dispersion polymer in the polylactic acid resin composition is 0.1% by weight to 10% by weight. In one embodiment, the filler is at least one selected from talc and mica. According to another aspect of the present invention, there is provided a method for producing the polylactic acid resin composition, comprising melt-kneading a polylactic acid resin and a filler granule, the filler granule containing the filler and the filler dispersant and / or the filler dispersion polymer, and the filler content in the filler granule is 80 to 99.9 parts by weight per 100 parts by weight of the filler granule. According to another aspect of the present invention, there is provided a molded article formed from the polylactic acid resin composition. In one embodiment, the molded article has a flexural modulus at 23° C. of 10 GPa or more. In one embodiment, the molded article has a deflection temperature under load of 120° C. or higher under a load of 0.45 MPa. According to another aspect of the present invention, there is provided an injection-molded article formed from the above polylactic acid resin composition. According to another aspect of the present invention, there is provided an extrusion molded article formed from the above polylactic acid resin composition. According to another aspect of the present invention, there is provided a sheet-shaped object formed from the above polylactic acid resin composition. According to another aspect of the present invention, there is provided a 3D printer model formed from the above polylactic acid resin composition. Effect of the Invention

[0007] According to the present invention, it is possible to provide a resin composition which is excellent in filler-attributable properties and has excellent productivity during molding, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] A. Polylactic acid resin composition A-1. Overview of polylactic acid resin composition The polylactic acid resin composition of the present invention contains a polylactic acid resin and a filler. The polylactic acid resin composition further contains a filler dispersant and / or a filler dispersion polymer. The filler content in the polylactic acid resin composition is 30% by weight to 70% by weight. The "filler content in the polylactic acid resin composition" is a weight percentage based on the total solid content in the polylactic acid resin composition.

[0009] Since the polylactic acid resin composition of the present invention contains a high content of filler, it is possible to form a molded product having excellent mechanical properties (for example, rigidity, dimensional stability (low molding shrinkage rate, low linear expansion coefficient, low warpage)) while using polylactic acid resin as the main component. In addition, the polylactic acid resin composition can be advantageously used from the viewpoints of heat resistance (heat distortion temperature resistance), appearance, colorability (coloring to bright colors is possible), filler dispersion, and composition uniformity. In addition, the polylactic acid resin composition is also excellent in production speed when produced by melt kneading. Furthermore, the polylactic acid resin composition is advantageous in that it can be composed of natural or biodegradable materials. The polylactic acid resin composition of the present invention is excellent in rigidity and heat resistance, and also has excellent appearance of the molded product, so it can be widely used as a raw material for industrial products such as high rigidity / high heat resistant parts (for example, fan parts, air conditioner outlets), high heat resistant / high rigidity trays (for example, microwave compatible shaping containers), and high rigidity / high heat resistant 3D modeling filaments.

[0010] In addition, in the polylactic acid resin composition, the crystallization rate of the polylactic acid resin is high, and the moldability during injection molding is excellent, and the molding cycle can be shortened. The degree of crystallization of the polylactic acid resin composition can be evaluated by differential scanning calorimetry (DSC). Here, differential scanning calorimetry is a method for measuring the endothermic heat of melting of polylactic acid crystals and the exothermic heat of recrystallization in a series of operations in which 5 to 10 mg of a sample is heated from room temperature to 200°C at a constant heating rate, held at 200°C for 5 minutes, and then cooled to room temperature under a constant temperature drop rate condition. Here, the faster the temperature drop rate at which the exothermic peak of recrystallization occurs in the temperature drop process, or the higher the temperature range at which it occurs, the more crystallization becomes possible during molding, and the molding speed (molding cycle) can be increased. In the polylactic acid resin composition, the exothermic peak derived from this crystallization is preferably 10 J / g or more in terms of polylactic acid, more preferably 20 J / g or more, and even more preferably 25 J / g or more. When the exothermic peak due to the crystallization is 10 J / g or more in terms of polylactic acid, excellent heat resistance can be exhibited by the progress of crystallization. Note that the term "polylactic acid equivalent" used here refers to the value obtained by dividing the heat value of the exothermic peak by the content of polylactic acid contained in the resin composition sample.

[0011] The polylactic acid resin composition of the present invention having the above-mentioned excellent properties can be obtained, for example, by forming a filler granule containing the above-mentioned filler and a filler dispersant and / or a filler dispersion polymer, and then mixing the filler granule with a polylactic acid resin (for example, by melt kneading). By adopting such a production method, the workability of adding the filler and the filler dispersibility are significantly improved, making it possible to incorporate a high content of filler.

[0012] In one embodiment, a molded article is provided that is formed from the polylactic acid resin composition. The molded article has a flexural modulus of preferably 10 GPa or more, more preferably 12 GPa or more, and even more preferably 15 GPa or more at 23°C. The flexural modulus is measured in accordance with ISO178. The molded article can be obtained, for example, by injection molding using pellets of the polylactic acid resin composition, as described below.

[0013] The deflection temperature under load of 0.45 MPa of a molded article formed from the polylactic acid resin composition is preferably 120° C. or higher, more preferably 130° C. or higher, even more preferably 140° C. or higher, and particularly preferably 150° C. or higher. The deflection temperature under load is measured in accordance with ISO 75 using a dumbbell-shaped test piece (type 1A multipurpose test piece).

[0014] The tensile strength of the molded article formed from the polylactic acid resin composition at 23° C. is preferably 35 MPa or more, more preferably 40 MPa or more, and even more preferably 50 MPa or more. The tensile strength and critical elongation described below are measured using a dumbbell-shaped test piece (type 1A multipurpose test piece) in accordance with ISO527 at a tensile speed of 5 mm / min.

[0015] In the above polylactic acid resin composition, the higher the temperature at which the exothermic peak of recrystallization occurs during the cooling process, the shorter the molding cycle can be, and according to the above-mentioned DSC measurement, when cooled from a temperature of 200°C at a rate of 10°C / min, the exothermic peak of recrystallization is preferably 95°C or higher, more preferably 100°C or higher, and even more preferably 105°C or higher.

[0016] A-2. Polylactic acid resin The polylactic acid resin may be any suitable polylactic acid resin, which may have the same properties as synthetic resins under normal use conditions, may be in the same condition as synthetic resins, and exhibits degradability under specific waste environments.

[0017] The polylactic acid resin may be a copolymer containing a structural unit derived from lactic acid, in addition to polylactic acid (homopolymer). In one embodiment, the polylactic acid resin may be a copolymer of lactic acid and hydroxycarboxylic acid. Examples of hydroxycarboxylic acid include glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, and 6-hydroxycaproic acid. As the polylactic acid resin, a polylactic acid resin having a high L-lactic acid ratio is preferably used because it has a high melting point. The L-lactic acid ratio of the polylactic acid resin is preferably 96% or more, more preferably 98% or more, and even more preferably 98.6% or more.

[0018] The content of the polylactic acid resin in the polylactic acid resin composition is preferably 31% by weight to 69% by weight, more preferably 35% by weight to 65% by weight, and further preferably 40% by weight to 60% by weight. Note that the "content of the polylactic acid resin in the polylactic acid resin composition" is a weight percentage based on the total solid content in the polylactic acid resin composition.

[0019] A-3. Filler As the filler, any appropriate filler can be used depending on the desired properties.

[0020] Examples of properties and effects that can be imparted by the above-mentioned fillers include weight increase or weight reduction, reinforcement (increased rigidity, increased elastic modulus, increased strength), dimensional stability, molding cycle (crystallization rate), degree of crystallinity, thermal conductivity, electrical conductivity, magnetism, piezoelectricity, vibration damping, sound insulation, sliding properties, heat insulation, electromagnetic wave absorption, light reflectivity, light scattering, heat radiation, flame retardancy, radiation protection, ultraviolet protection, moisture removal, dehydration, deodorization, gas absorption, gas barrier, anti-blocking, oil absorption, antibacterial properties, promotion of biodegradation, improved bio content (increased ratio of components derived from natural products), and the like.

[0021] For example, calcium carbonate, talc, silica, and clay are suitable for increasing the weight. For reinforcing purposes, wollastonite, potassium titanate, xonotlite, gypsum fiber, aluminum borate, fibrous magnesium compound (MOS), aramid fiber, various fiber systems, carbon fiber, glass fiber, talc, mica, glass flakes, polyoxybenzoyl whiskers, and the like are suitable. For providing antibacterial properties, catechin, silver ion-supported zeolite, copper phthalocyanine, and the like are suitable. For providing gas barrier properties, synthetic mica systems, clay / synthetic mica nanofillers, and the like are suitable. For reducing weight, balloon systems such as silica balloons, glass balloons, cenospheres, perlite, and shirasu balloons are suitable. For providing electrical conductivity, carbon black, graphite, carbon fiber, metal powder, metal fiber, and metal foil are suitable. For the purpose of imparting magnetism, various magnetic materials, various ferrites, magnetic iron oxide, samacobalt (Sm-Co), Nd-Fe-B, etc. are suitable. For the purpose of imparting thermal conductivity, alumina, AlN, BN, BeO, etc. are suitable. For the purpose of imparting piezoelectricity, barium titanate, lead zirconate titanate (PZT), etc. are suitable. For the purpose of imparting vibration damping properties, mica, graphite, potassium titanate, xonotlite, carbon fiber, ferrite, etc. are suitable. For the purpose of imparting sound insulation properties, iron powder, lead powder, barium sulfate, etc. are suitable. For the purpose of imparting sliding properties, graphite, hexagonal BN, molybdenum sulfide, Teflon (registered trademark) powder, talc, high molecular weight polyethylene, etc. are suitable. For the purpose of imparting electromagnetic wave absorption, electromagnetic wave absorbing ferrite, graphite, charcoal powder, carbon microcoil (CMC), carbon nanotube (CNT), PZT, etc. are suitable. For the purpose of imparting light reflection and light scattering, titanium oxide, glass beads, calcium carbonate, aluminum powder, mica, etc. are suitable. For the purpose of imparting heat radiation, magnesium oxide, hydrotalcite, MOS, alumina, charcoal powder, etc. are suitable. For the purpose of flame retardancy, antimony oxide, aluminum hydroxide, magnesium hydroxide, zinc borate, red phosphorus, zinc carbonate, hydrotalcite, dawsonite, bromine-based flame retardants, phosphorus-based flame retardants, etc. are suitable. For the purpose of radiation protection, lead powder, barium sulfate, etc. are suitable.For the purpose of "ultraviolet protection", titanium oxide, zinc oxide, iron oxide, etc. are suitable. For the purpose of dehumidification and dehydration, calcium oxide, magnesium oxide, etc. are suitable. For the purpose of deodorization and gas absorption, zeolite, activated clay, etc. are suitable. For the purpose of anti-blocking (prevention of film pressure adhesion), silica, calcium carbonate, talc, spherical microparticles (silicone or acrylic beads), etc. are suitable. For the purpose of oil absorption (printing ink absorption, quick drying, etc.), algae-shaped calcium carbonate, algae-shaped xonotlite, etc. are suitable. For the purpose of water absorption, water-absorbing polymer gel, calcium oxide, magnesium oxide, etc. are suitable. For the purpose of increasing the bio content, cellulosic materials (wood flour, wood fiber, sawdust, wood chips, newsprint, paper, flax, hemp, wheat straw, rice husks, kenaf, jute, sisal, peanut shells, soybean hulls, etc.), starch, natural rubber, etc. are suitable.

[0022] The size of the filler can be any appropriate size. The particle size of the filler is, for example, 10 nm to 100 μm. The size of the filler can be determined by a laser diffraction method.

[0023] In one embodiment, a silicate compound is used as the filler. For example, talc, mica, and wollastonite can be preferably used as the silicate compound. In one embodiment, the filler is at least one selected from talc and mica. Talc is particularly preferred. The silicate compound not only has an effect as a reinforcing material for the polylactic acid resin composition, but also has an effect as a crystal nucleating agent for polylactic acid, and the use of the silicate compound can increase the crystallinity of the polylactic acid and at the same time increase the crystallization rate. As a result, the heat resistance of the polylactic acid resin composition can be increased and the solidification time can be shortened, making it possible to improve the moldability.

[0024] As described above, the filler content in the polylactic acid resin composition is 30% by weight to 70% by weight. The filler content in the polylactic acid resin composition is preferably 35% by weight to 65% by weight, and more preferably 40% by weight to 60% by weight.

[0025] A-4. Filler dispersant In one embodiment, the filler dispersant is a compound composed of a hydrophobic group and a hydrophilic group. The hydrophilic / hydrophobic balance can be controlled by adjusting the degree of esterification of the compound to be the filler dispersant, the type of fatty acid (presence or absence of a hydroxyl group, saturated or unsaturated fatty acid, alkyl chain length), and the degree of polymerization. The hydrophilic / hydrophobic balance can be any appropriate balance depending on the type of the filler, the type of resin to be combined with the granular filler composition, and the like.

[0026] The content of the filler dispersant in the polylactic acid resin composition is preferably 0.1% by weight to 10% by weight, more preferably 1% by weight to 8% by weight, and even more preferably 1% by weight to 5% by weight. Within such a range, a resin composition having excellent filler-attributable properties can be obtained, and a polylactic acid resin composition having excellent productivity and filler dispersibility can be obtained. The "content of the filler dispersant in the polylactic acid resin composition" is a weight percentage based on the total solid content in the polylactic acid resin composition.

[0027] The total content of the filler dispersant and the filler dispersion polymer in the polylactic acid resin composition is preferably 0.1% by weight to 10% by weight, more preferably 1% by weight to 8% by weight, and even more preferably 1% by weight to 5% by weight. Within such a range, a resin composition having excellent filler-attributable properties can be obtained, and a polylactic acid resin composition having excellent productivity and filler dispersibility can be obtained. Note that the "total content of the filler dispersant and the filler dispersion polymer" means the content of the filler dispersion polymer when the polylactic acid resin composition does not contain a filler dispersant, and means the content of the filler dispersant when the polylactic acid resin composition does not contain a filler dispersion polymer.

[0028] In one embodiment, the filler dispersant is an ester compound. In one embodiment, the filler dispersant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, fatty acid amides, polyglycerin fatty acid esters, condensed hydroxy fatty acids, and alcohol esters of condensed hydroxy fatty acids. Among them, at least one selected from the group consisting of polyglycerin fatty acid esters, condensed hydroxy fatty acids, and alcohol esters of condensed hydroxy fatty acids is particularly preferably used because it not only has excellent filler dispersion function but also has the effect of promoting crystallization in the polylactic acid resin composition.

[0029] The polyhydric alcohol fatty acid ester is an ester compound composed of a polyhydric alcohol and a fatty acid, and can be obtained by esterification of the polyhydric alcohol and a fatty acid.

[0030] Examples of the polyhydric alcohol include alkane polyols such as pentaerythritol and glycerin; polyalkane polyols which are polymers of the alkane polyols; sugars such as sucrose; and sugar derivatives represented by sugar alcohols such as sorbitol and mannitol. These alcohols may be used alone or in combination of two or more. Any appropriate fatty acid may be used as the fatty acid. In one embodiment, a fatty acid having 8 or more carbon atoms (preferably 8 to 24 carbon atoms, more preferably 10 to 22 carbon atoms) is used. Specific examples of fatty acids include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, nonadecanoic acid, arachic acid, gadoleic acid, eicosadienoic acid, arachidonic acid, behenic acid, erucic acid, docosadienoic acid, lignoceric acid, isostearic acid, ricinoleic acid, 12-hydroxystearic acid, 9-hydroxystearic acid, 10-hydroxystearic acid, hydrogenated castor oil fatty acid (a fatty acid containing a small amount of stearic acid and palmitic acid in addition to 12-hydroxystearic acid), etc. Among them, palmitic acid and stearic acid are preferable. Only one type of fatty acid may be used, or two or more types may be used in combination.

[0031] The fatty acid amide is a compound having a structure in which a fatty acid and ammonia or a primary or secondary amine are dehydrated and condensed. The fatty acid amide is not particularly limited, but specifically includes saturated fatty acid monoamides such as lauric acid amide, palmitic acid amide, stearic acid amide, and behenic acid amide, unsaturated fatty acid monoamides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide, substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide, methylol amides such as methylol stearic acid amide and methylol behenic acid amide, methylene bis stearic acid amide, ethylene bis capric acid amide, ethylene bis lauryl ... Examples of the fatty acid amide include saturated fatty acid bisamides such as uric acid amide, ethylene bisstearic acid amide, ethylene bisisostearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipic acid amide, and N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, and N,N'-dioleyl adipic acid amide; and aromatic bisamides such as m-xylylene bisstearic acid amide. These fatty acid amides may be used alone or in combination of two or more. Among these, those having a melting temperature in the range of about 70°C to 120°C are particularly preferred.

[0032] The polyglycerol fatty acid ester is an ester compound composed of polyglycerol and a fatty acid.

[0033] As the polyglycerin, any suitable polyglycerin can be used.Specific examples of the polyglycerin include diglycerin, triglycerin, tetraglycerin, pentaglycerin, hexaglycerin, heptaglycerin, octaglycerin, nonaglycerin, decaglycerin, eicosaglycerin, and tetracontaglycerin.Of these, diglycerin, triglycerin, pentaglycerin, or decaglycerin is preferred.Only one type of polyglycerin may be used, or two or more types may be used in combination.

[0034] Any appropriate fatty acid may be used as the fatty acid. In one embodiment, a fatty acid having 8 or more carbon atoms (preferably 8 to 24, more preferably 10 to 22) is used. Specific examples of fatty acids include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, nonadecanoic acid, arachic acid, gadoleic acid, eicosadienoic acid, arachidonic acid, behenic acid, erucic acid, docosadienoic acid, lignoceric acid, isostearic acid, ricinoleic acid, 12-hydroxystearic acid, 9-hydroxystearic acid, 10-hydroxystearic acid, and hydrogenated castor oil fatty acid (a fatty acid containing small amounts of stearic acid and palmitic acid in addition to 12-hydroxystearic acid). Among these, palmitic acid and stearic acid are preferred. Only one type of fatty acid may be used, or two or more types may be used in combination.

[0035] Specific examples of the polyglycerol fatty acid ester include diglycerol palmitate, diglycerol stearate, diglycerol oleate, decaglycerol palmitate, decaglycerol stearate, decaglycerol oleate, etc. These may be used alone or in combination of two or more.

[0036] The fatty acid esterification rate of the polyglycerol fatty acid ester is preferably 35% or more, more preferably 50% to 70%. Within this range, a filler granule having excellent production stability can be obtained. In addition, the filler granule has excellent dispersibility in resins (especially thermoplastic resins). The esterification rate (%) is expressed by the formula: esterification rate (%) = (mol number of constituent fatty acids / number of hydroxyl groups of polyglycerol) x 100.

[0037] The polyglycerol fatty acid ester can be obtained by any suitable method. For example, it can be obtained by reacting polyglycerol with a fatty acid in the presence or absence of a catalyst (e.g., phosphoric acid, p-toluenesulfonic acid, caustic soda) at 100°C to 300°C (preferably 120°C to 260°C) while removing the generated water from the system. The reaction is preferably carried out in the presence of an inert gas. It may also be carried out in an azeotropic solvent such as toluene or xylene.

[0038] The condensed hydroxy fatty acid can be obtained by dehydration condensation of a hydroxy fatty acid. The condensed hydroxy fatty acid can be obtained, for example, by adding an alkali catalyst such as caustic soda to a hydroxy fatty acid and removing reaction water under heating to perform dehydration condensation.

[0039] The condensed hydroxy fatty acid is a condensation product of a hydroxy fatty acid, and the degree of condensation is preferably not less than 2, more preferably not less than 4. The upper limit of the degree of condensation of the condensed hydroxy fatty acid is, for example, 20. The degree of condensation can be calculated from the acid value of the raw hydroxy fatty acid and the acid value after the condensation reaction.

[0040] The above-mentioned hydroxy fatty acid is a fatty acid having one or more hydroxyl groups in the molecule.Specific examples of hydroxy fatty acid include ricinoleic acid, 12-hydroxystearic acid, savinic acid, 2-hydroxytetradecanoic acid, iprolic acid, 2-hydroxyhexadecanoic acid, yarapinolic acid, uniperilic acid, ambrettolic acid, aluritic acid, 2-hydroxyoctadecanoic acid, 18-hydroxyoctadecanoic acid, 9,10-dihydroxyoctadecanoic acid, camrolenoic acid, ferronic acid, and cerebronic acid.Hydroxy fatty acid may be used alone or in combination of two or more.

[0041] The alcohol ester of the condensed hydroxy fatty acid can be obtained by esterification reaction of the condensed hydroxy fatty acid with alcohol. The alcohol ester of the condensed hydroxy fatty acid can be obtained, for example, by mixing the condensed hydroxy fatty acid with alcohol, adding an alkali catalyst such as caustic soda or an acid catalyst such as phosphoric acid to the resulting mixture, and removing reaction water under heating. The progress of esterification during this reaction can be confirmed by measuring the acid value, saponification value, hydroxyl value, etc. In the condensed hydroxy fatty acid used here, the condensation degree is preferably 2 or more, more preferably 4 or more, as described above.

[0042] Examples of the alcohol include monohydric alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; dihydric alcohols such as ethylene glycol and propylene glycol. In addition, polyhydric alcohols may be used as the alcohol. Examples of the polyhydric alcohol include alkane polyols such as pentaerythritol and glycerin; polyalkane polyols which are polymers of the alkane polyols; sugars such as sucrose; and sugar derivatives represented by sugar alcohols such as sorbitol and mannitol. These alcohols may be used alone or in combination of two or more.

[0043] Specific examples of the condensed hydroxy fatty acid and its alcohol ester include condensed ricinoleic acid obtained by dehydration condensation of ricinoleic acid, condensed 12-hydroxystearic acid obtained by dehydration condensation of 12-hydroxystearic acid, condensed ricinoleic acid hexaglycerin ester which is an ester of condensed ricinoleic acid and hexaglycerin of glycerin 6 polymer, condensed ricinoleic acid tetraglycerin ester which is an ester of condensed ricinoleic acid and tetraglycerin of glycerin 4 polymer, condensed 12-hydroxystearic acid propylene glycol ester which is an ester of condensed 12-hydroxystearic acid and propylene glycol, and condensed linoleic acid propylene glycol ester which is an ester of condensed ricinoleic acid and propylene glycol, etc. These may be used alone or in combination of two or more.

[0044] The polyglycerol fatty acid ester, condensed hydroxy fatty acid, and alcohol ester of condensed hydroxy fatty acid may be commercially available. Examples of commercially available products include "Chirabazol P-4", "Chirabazol VR-01", "Chirabazol VR-08" (polyglycerol fatty acid ester), "Chirabazol H-818" (alcohol ester of condensed hydroxy fatty acid), etc., manufactured by Taiyo Kagaku Co., Ltd.

[0045] The weight average molecular weight of the filler dispersant is preferably 800 or more, more preferably 800 to 4000. Within such a range, a filler granule can be preferably formed, and a polylactic acid resin composition having a high filler content can be obtained. More specifically, a filler granule having excellent granulation properties, thermal stability, and dispersibility can be obtained. The weight average molecular weight can be measured by the intrinsic viscosity method.

[0046] A-5. Polymers for dispersing fillers The polylactic acid resin composition may contain a filler dispersion polymer for the purpose of improving the dispersibility of the filler. The filler dispersion polymer may also have the effect of improving the interfacial adhesion between the filler and the polylactic acid resin.

[0047] The filler dispersion polymer may be at least one selected from the group consisting of polyethylene resins, polypropylene resins, polyvinyl alcohol resins, polystyrene resins, polyacrylate resins, polymethacrylate resins, and water-soluble polysaccharides. Among these, polyvinyl alcohol resins and water-soluble polysaccharides are particularly preferably used because they are highly compatible with polylactic acid resins, have excellent filler dispersion function, and are biodegradable themselves.

[0048] The content of the filler dispersion polymer in the polylactic acid resin composition is preferably 0.1 to 10% by weight, more preferably 1 to 8% by weight, and further preferably 1 to 5% by weight. The "content of the filler dispersion polymer in the polylactic acid resin composition" is a weight percentage based on the total solid content in the polylactic acid resin composition.

[0049] Specific examples of the polyethylene resin used as the filler dispersion polymer include high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), polyolefin elastomers (POE), polyolefin copolymers (e.g., ethylene-butene, ethylene-octene, etc.), modified polyolefins (e.g., modified maleic anhydride, acrylic acid, etc.), and functional polyolefin copolymers including polyolefin-based ionomers.

[0050] Specific examples of the polypropylene resin used as the filler dispersion polymer include homopolypropylene (h-PP), block polypropylene (b-PP), random polypropylene (r-PP), polypropylene copolymer, and modified polypropylene (e.g., modified with maleic anhydride, acrylic acid, etc.).

[0051] Specific examples of the polyvinyl alcohol resin used as the filler dispersion polymer include ethylene-vinyl alcohol copolymer (EVOH; EVAL (registered trademark) manufactured by Kuraray Co., Ltd.), butenediol-vinyl alcohol copolymer (BVOH; Nichigo G-Polymer (registered trademark) manufactured by Mitsubishi Chemical Corporation), and the like.

[0052] Specific examples of the polystyrene-based resin used as the filler dispersion polymer include polystyrene, polystyrene copolymers (e.g., high-impact polystyrene, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, methacrylic acid-styrene copolymer, etc.), and styrene-based thermoplastic elastomers (e.g., SIS, SEBS, SEPS, SBS, etc.).

[0053] Specific examples of the polyacrylate resin and polymethacrylate resin as the filler dispersion polymer include polyacrylate, polymethacrylate, acrylate copolymer, and methacrylate copolymer.

[0054] The water-soluble polysaccharide refers to a water-soluble compound composed of long chains of monosaccharides such as glucose, mannose, etc. In one embodiment, the water-soluble polysaccharide is a water-soluble carbohydrate composed of 10 or more monosaccharides linked together.

[0055] In one embodiment, the water-soluble polysaccharide may be a polymeric substance of natural origin, such as a water-soluble polysaccharide derived from a plant (seed, sap, fruit, etc.), seaweed, or microorganism.

[0056] Specific examples of the water-soluble polysaccharides include pullulan, dextrin, chitosan, tamarind seed gum, guar gum, locust bean gum, gum arabic, karaya gum, pectin, cellulose, konjac mannan, soybean polysaccharides, carrageenan, agar, tragacanth gum, alginic acid, xanthan gum, gellan gum, Agrobacterium succinoglycan, carboxymethylcellulose, cationized guar gum, etc. Among these, pullulan or dextrin is preferred, and pullulan is more preferred.

[0057] Commercially available products may be used as the filler dispersion polymer. Examples of commercially available products include Chemipearl (registered trademark) manufactured by Mitsui Chemicals, Inc., HYPOD (registered trademark) manufactured by Dow Chemical Company, AQUACER (registered trademark) manufactured by BYK Japan, ZAIKXEN (registered trademark) manufactured by Sumitomo Seika Chemicals, Saiden Glue (registered trademark) manufactured by Saiden Chemical, Inc., and Saibinol (registered trademark) manufactured by Saiden Chemical, Inc.

[0058] A-6. Other ingredients The polylactic acid resin composition may further contain any other appropriate components (additives) as necessary. Examples of additives include antioxidants, light stabilizers, foaming agents, UV absorbers, foaming agents, antiblocking agents, heat stabilizers, impact modifiers, antibacterial agents, compatibilizers, plasticizers, tackifiers, processing aids, lubricants, coupling agents, flame retardants, oxygen scavengers, and colorants. The additives may be added at any appropriate timing in the production process of the polylactic acid resin composition, for example, in the form of liquid, powder, pellets, granules, or master batch.

[0059] In one embodiment, the polylactic acid resin composition may further contain a resin other than the polylactic acid resin. Examples of the resin include aliphatic polyester resins (e.g., homopolymers or copolymers of polycaprolactone, polyethylene succinate, polybutylene succinate adipate, polyhydroxyvalerate, etc., or modified products of these homopolymers or copolymers), aliphatic / aromatic polyester resins (e.g., block polymers or random polymers of aliphatic carboxylic acids or hydroxy acids, aromatic dicarboxylic acids and 1,3-propanediol, etc.), and polyvinyl alcohol resins (e.g., polyvinyl alcohol, polyvinyl acetate, polyvinyl butyrate, ethylene / vinyl alcohol copolymers, etc.). Natural rubber and the like can also be used as a naturally derived biodegradable resin.

[0060] B. Method for producing polylactic acid resin composition In one embodiment, the polylactic acid resin composition can be obtained by melt-kneading the polylactic acid resin, the filler, and the filler dispersant and / or the filler dispersion polymer. Any appropriate method can be adopted as the melt-kneading method. For example, a kneader, a Banbury mixer, a roll, or a single-screw or multi-screw extruder having two or more screws can be used. A twin-screw extruder is preferably used. The melt-kneaded composition can be pelletized. In one embodiment, the melt-kneading is performed in a temperature range of 80°C to 170°C (preferably 100°C to 160°C).

[0061] In one embodiment, the polylactic acid resin composition is obtained by melt-kneading the filler granules containing the filler and the filler dispersant and / or filler dispersion polymer with the polylactic acid resin. By adopting such a manufacturing method, the workability of adding the filler and the filler dispersibility are significantly improved, and it is possible to contain a high content of filler. More specifically, since the filler granules are extremely stable when put into an extruder or other device, the productivity (compound processing speed per hour) of the filler-containing resin composition can be dramatically improved by using the filler granules. Furthermore, when the filler granules are used, the filler dispersibility and moldability (fluidity) are improved, so that the polylactic acid resin composition obtained by using the filler granules can be obtained by melt-kneading by low-load extrusion, that is, melt-kneading in which excessive heat generation of the resin is suppressed, even though the filler is contained at a high concentration. As a result, the polylactic acid resin composition is inhibited from thermally deteriorating, and has excellent mechanical properties and moldability.

[0062] (Filler granules) The filler granules can be produced by any suitable method. The filler granules can be obtained, for example, by subjecting a mixture containing the filler, the filler dispersant, and / or the binder component to a semi-wet granulation method. More preferably, the filler granules can be obtained by subjecting a mixture containing the filler, the filler dispersant, and the binder component to a semi-wet granulation method. The filler and filler dispersant described in Section A can be used.

[0063] The content of the filler in the filler granules is preferably 80 parts by weight to 99.9 parts by weight, more preferably 82 parts by weight to 99 parts by weight, even more preferably 85 parts by weight to 98 parts by weight, particularly preferably 87 parts by weight to 97 parts by weight, and most preferably 90 parts by weight to 96 parts by weight, relative to 100 parts by weight of the filler granules.

[0064] In one embodiment, the above-mentioned filler dispersion polymer is used as the binder component. In another embodiment, a swelling clay mineral is used as the binder component.

[0065] In one embodiment, the filler-dispersing polymer is subjected to mixing in the form of a polymer liquid (polymer solution or polymer dispersion) containing the filler-dispersing polymer.

[0066] In one embodiment, the method for producing the filler granules includes a mixing step of mixing the filler, the binder component, and the filler dispersant, a granulation step of granulating the mixture obtained through the mixing step to obtain a granule precursor, and a drying step of drying the granule precursor.

[0067] In the mixing step, water may be further mixed in. The water to be added is not particularly limited, and for example, tap water, distilled water, ion-exchanged water, hard water, soft water, etc. may be used.

[0068] The amount of water mixed is usually 1 to 30 parts by weight, preferably 3 to 25 parts by weight, and more preferably 5 to 20 parts by weight, based on 100 parts by weight of the filler in the filler granules.

[0069] In the mixing step, it is preferable to mix the components at room temperature and homogenize them using any suitable mixer, such as a Henschel mixer, a powder kneader (KDH, KDA, CKD, CPM) (Dalton), a Spartan mixer (SPM) (Dalton), or a SP granulator (SPG) (Dalton).

[0070] The mixing time in the mixing step can be any appropriate time depending on the type of components, the type of mixer, the component blending ratio, etc. In the mixing step, the mixing time is set so that each component is uniformly dispersed. In a high-speed mixer such as a Henschel mixer or a Spartan mixer, the mixing time can be 1 to 10 minutes. On the other hand, in the case of a powder kneader, a processing time of several minutes to 60 minutes may be required.

[0071] In the granulation step, a compression granulation method is preferably used. In addition, in the granulation step, a semi-wet granulation method can be preferably used. Examples of the compression granulation method / semi-wet granulation method include a disk pelleting method, a tableting method, and a briquetting method. From the viewpoint of the balance between productivity and the quality of the resulting filler granules, the disk pelletizer method is preferably adopted.

[0072] The basic structure of a disk pelletizer is one or two disks with many holes of 2 mm to 30 mm, and a roller for pressure-feeding the raw material into the holes of the disk. The raw material supplied between the disk and the roller, or between two disks, is pressed into the holes of the disk as the roller rotates, and a cylindrical extrudate is formed. Here, the disk hole is tapered, and a compressive stress is applied from the outer periphery of the die hole in the process of the filler mixture passing through the hole. The length of this tapered hole is called the effective length. The extruded granulated material precursor is cut by a cutter or the like on the back side of the disk to obtain a pellet-shaped filler granulated material. The length of the granulated material precursor (resulting in a filler granulated material) can be adjusted by the distance between the back side of the disk and the cutter and the number of rotations of the roller.

[0073] More specifically, the disc pelleter type includes a roller disc die type, a roller ring die type, a double die type, a flat die type, etc. An example of a commercially available disc pelleter type granulator is the Disc Pelletter F Series manufactured by Dalton.

[0074] Any suitable drying method can be used in the drying step. After the drying step, a filler granule from which fine powder has been removed can be obtained by a vibrating sieve or the like. Any suitable drying equipment can be used in the drying step. For example, a vibrating fluidized dryer is preferred because it can perform drying efficiently in a short time, and examples of such equipment include the VDF series vibrating fluidized dryers manufactured by Dalton.

[0075] In the present invention, various molded articles are provided using the polylactic acid resin composition. For example, injection molded articles, extrusion molded articles, sheets, 3D printer molded articles, etc. can be provided. In addition, shaped articles (vacuum molded articles, press molded articles, sheet-like shaped articles, etc.) can be obtained from the sheets. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, parts and percentages are based on weight unless otherwise specified.

[0077] [Production Example 1] Production of filler granules MB-1 80 parts by weight of filler (talc powder; Asada Flour Milling Co., Ltd., product name "JM-300"; average particle size: 4.7 μm; in the table, "B-1") was added to a powder kneader (Dalton Co., Ltd., product name "KDHJ-10"; processing capacity: 6 L), and while stirring with a stirring blade at a rotation speed of 30 rpm, 20 parts by weight of polymer dispersion (polyolefin dispersion (aqueous PE dispersion); Mitsui Chemicals, Inc., product name "Chemipearl A100"; polyolefin solids concentration: 40 wt %; average particle size of polyolefin particles: 4 μm; in the table, "D-1") was added to the powder kneader. Then, stirring was performed for 6 minutes to obtain mixture A. Mixture A was put into a disk pelleter (manufactured by Dalton, product name "Disc Pelleter F-5 / 11-175; capacity: 5 L") to obtain a pellet-shaped granulated precursor. At this time, the hole diameter of the die was 3 mmφ, the thickness of the die plate was 15 mm, the effective length of the die hole was 10 mm, and the rotation speed of the roller of the disk pelleter was 108 rpm. The obtained granule precursor was dried at 140° C. for 6 hours using a hot air circulation type dryer to obtain filler granule MB-1.

[0078] [Production Example 2] Production of filler granules MB-2 20 parts by weight of polymer dispersion ("Chemipearl A100"; in the table, "D-1") and 3 parts by weight of filler dispersant (polyglycerol condensed hydroxy fatty acid ester; Taiyo Kagaku Co., Ltd., product name "Chirabazol H818"; in the table, "C-1") were added to a 1 L plastic container and stirred for 20 minutes at room temperature using a stirring blade to obtain mixture B. Next, 80 parts by weight of filler (talc powder "JM-300"; in the table, "B-1") were added to a powder kneader (KDHJ-10), and mixture B was added to the powder kneader while stirring with the stirring blade at a rotation speed of 30 rpm. Then, stirring was carried out for 6 minutes to obtain mixture C. Mixture C was put into a disk pelleter (manufactured by Dalton, product name "Disc Pelleter F-5 / 11-175; capacity: 5 L") to obtain a pellet-shaped granulated precursor. At this time, the hole diameter of the die was 3 mmφ, the thickness of the die plate was 15 mm, the effective length of the die hole was 10 mm, and the rotation speed of the roller of the disk pelleter was 108 rpm. The obtained granule precursor was dried at 140° C. for 6 hours using a hot air circulation type dryer to obtain filler granule MB-2.

[0079] [Production Examples 3 to 5] Production of filler granules MB-3 to MB-5 Filler granules MB-3 to MB-5 were obtained in the same manner as in Production Example 2, except that the filler dispersing agents shown in Table 1 were used. Specific details of each component used in the Production Examples are as shown in Table 2. Note that Table 1 shows the final component composition ratios after drying for MB-1 to MB-14, calculated from the blended compositions.

[0080] [Production Example 6] Production of filler granules MB-6 Filler granules MB-6 were obtained in the same manner as in Production Example 1, except that 20 parts by weight of a polymer liquid (aqueous solution of water-soluble vinyl alcohol resin (BVOH); manufactured by Mitsubishi Chemical Corporation, product name "Nichigo G-polymer AZF8035Q"; saponification degree 98.0 mol% or more; melting point: 172°C; polymer concentration: 15 weight%: "D-2" in the table) was used instead of the polymer dispersion liquid "D-1".

[0081] [Production Example 7] Production of filler granules MB-7 Filler granules MB-7 were obtained in the same manner as in Production Example 2, except that 20 parts by weight of a polymer liquid (aqueous solution of water-soluble vinyl alcohol resin (BVOH); manufactured by Mitsubishi Chemical Corporation, product name "Nichigo G-polymer AZF8035Q"; saponification degree 98.0 mol% or more; melting point: 172°C; polymer concentration: 15 weight%: "D-2" in the table) was used instead of the polymer dispersion liquid "D-1".

[0082] [Production Examples 8 to 10] Production of filler granules MB-8 to MB-10 Filler granules MB-8 to MB-10 were obtained in the same manner as in Production Example 7, except that the filler dispersing agents shown in Table 1 were used.

[0083] [Production Example 11] Production of filler granules MB-11 19.5 parts by weight of clean water and 1 part by weight of filler dispersant "C-1" were put into a 1L plastic container and stirred for 20 minutes at room temperature using a stirring blade to obtain a mixture D. Next, 80 parts by weight of filler (mica powder; manufactured by Chuzhou Grea Minerals Co., product name "GM-4"; average particle size: 18 μm; in the table, "B-2") and 0.5 parts by weight of swelling clay mineral (smectite; manufactured by Mizusawa Chemical Industries, Ltd., product name "Galleon Earth SH"; in the table, "D-3") were put into a powder kneader "KDHJ-10", and the mixture D was put into the powder kneader while stirring with a stirring blade at a rotation speed of 30 rpm. Then, a stirring process was performed for 6 minutes to obtain a mixture E. Mixture E was put into a disk pelleter (manufactured by Dalton, product name "Disc Pelleter F-5 / 11-175; capacity: 5 L") to obtain a pellet-shaped granulated precursor. At this time, the hole diameter of the die was 3 mmφ, the thickness of the die plate was 15 mm, the effective length of the die hole was 10 mm, and the rotation speed of the roller of the disk pelleter was 108 rpm. The obtained granule precursor was dried at 160° C. for 6 hours using a hot air circulation type dryer to obtain filler granule MB-11.

[0084] [Production Example 12] Production of filler granules MB-12 Filler granule MB-12 was obtained in the same manner as in Production Example 7, except that a starch derivative (manufactured by Saiden Chemical Co., Ltd., product name "Saiden Glue X-4"; evaporation residue 37%; "D-4" in the table) was used instead of the polymer dispersion "D-1".

[0085] [Production Example 13] Production of filler granules MB-13 Filler granules MB-13 were obtained in the same manner as in Production Example 7, except that mica powder "B-2" was used instead of filler "B-1".

[0086] [Production Example 14] Production of filler granules MB-14 Filler granules MB-14 were obtained in the same manner as in Production Example 13, except that wollastonite powder (manufactured by Kinsei Matec Co., Ltd., product name "SH-1800"; aspect ratio 10 to 20; "B-3" in the table) was used instead of filler "B-1".

[0087] [Table 1]

[0088] [Table 2]

[0089] [Example 1] 55 parts by weight of filler granules MB-1 and 45 parts by weight of polylactic acid (PLA; Nature Works, product name "Ingeo 4032D"; melting point 155-170 ° C; "A-1" in the table) were quantitatively fed into a twin-screw extruder (Toshiba Machine, product name "TEM18SS", L / D = 48) through a hopper installed at the most upstream position of the extruder, using a weight feeder independently, and continuously melt-kneaded (discharge: 5 kg / Hr) to obtain pellets of the resin composition. The cylinder temperature of the extruder was set to 200 ° C from the middle stage of the extruder onwards. In addition, the rotation speed of the main screw of the twin-screw extruder was set to 100 rpm. The melt-kneaded resin composition was extruded into a strand shape, cooled in a water-cooled bath, and made into pellets with a length of about 3 mm.

[0090] [Examples 2 to 10] Pellets of a polylactic acid resin composition were obtained in the same manner as in Example 1, except that the filler granules and polylactic acid shown in Table 3 were used in the amounts shown in Table 3.

[0091] [Table 3]

[0092] <Evaluation> The polylactic acid resin compositions obtained in Examples 1 to 10 were subjected to the following evaluations. The results are shown in Table 4. (1) Ash content measurement (unit: weight %) 1 to 3 g of pellets of the polylactic acid resin composition were collected and held in a crucible in an electric furnace at 600° C. for 3 hours, and the ash weight was calculated. (2) Dispersibility of fillers The pellets of the polylactic acid resin composition were rolled by a hot press to form a sheet having a thickness of about 0.5 mm. The remaining filler aggregates were visually observed through the sheet and evaluated according to the following criteria. AA: Good dispersion state with almost no filler agglomerates observed A: A state in which a trace amount of relatively small filler aggregates remain BB: A state in which a considerable number of relatively small filler aggregates remain. B: Large filler aggregates (Distribution order: AA>A>BB>B (left good)) (3) Crystallization temperature measurement (unit: °C) Using a differential scanning calorimeter (DSC) (Hitachi High-Tech Science, DSC6220), 5 to 10 mg of sample was heated from room temperature to 200°C at a constant heating rate, held at 200°C for 5 minutes, and then cooled to room temperature at a constant cooling rate of 10°C / min to measure the recrystallization temperature of polylactic acid crystals. (4) MFR (unit: g / 10 min) The melt mass flow rate (MFR) was measured and the fluidity was evaluated using a "Melt Indexer" manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with JIS K7210. The measurement conditions were 210°C and a load of 2.16 kg. (5) Tensile measurement The tensile strength (unit: MPa) and breaking elongation (unit: %) were measured at a pulling speed of 5 mm / min in accordance with ISO527. The test pieces used for the measurements were dumbbell-shaped test pieces (Type 1A multipurpose test pieces) molded from pellets of the polylactic acid resin composition using an injection molding machine (Toyo Machinery and Metals "SI-80W", mold clamping 100 tons) with a cylinder setting temperature of 200°C, a mold temperature of 110°C (both the fixed side and the moving side), and a cooling time of 60 seconds. (6) Bending measurement A bending test was carried out in accordance with ISO178 to measure the bending strength (unit: MPa) and bending modulus (unit: GPa). The test specimens for measurement were dumbbell-shaped test specimens cut out from the above-mentioned tensile measurements. (7) Heat deflection temperature measurement (unit: °C) The deflection temperature under load was measured under a load of 0.45 MPa in accordance with ISO 75. The test specimens used for the measurement were dumbbell-shaped test specimens cut out from the above tensile measurement. (8) Charpy impact test (unit: KJ / m 2 ) The Charpy impact strength of a notched test piece formed from the polylactic acid resin composition was measured in accordance with ISO 179. The test piece for measurement was cut out from the dumbbell-shaped test piece obtained in the tensile measurement described above. (9) Molding time of injection molded specimen (dumbbell test specimen) (unit: seconds) In the injection molding of the dumbbell-shaped test piece (Type 1A multipurpose test piece) for the tensile test, the total number of seconds was counted, including the cooling time of 60 seconds, the injection time, the pressure holding time, and the ejection time of the molded product. (10) Appearance of molded product The appearance of the dumbbell-shaped test pieces for the tensile test was classified into the following three categories. A: Glossy B: Dullness is observed C: Skin feels rough (Appearance ranking: A>B>C (left good)) (11) Warpage of injection-molded specimens (dumbbell test specimens) The dumbbell-shaped test piece for the tensile test (Type 1A multipurpose test piece) was placed on a horizontal plane, and one end of the dumbbell was pressed against the horizontal plane. The amount of lift (unit: mm) of the opposite end from the horizontal plane was measured and classified into the following three categories. AA: Almost no lifting is observed A: Floating less than 2mm B: Floating is 2mm or more but less than 4mm C: Lift is 5mm or more (Sled ranking: AA>A>B>C (left good)) (12) Specific gravity The specific gravity of the resin composition was measured using a specific gravity meter (manufactured by Shinko Denshi Co., Ltd., "DMA220H"). (13) Heat generation due to PLA crystallization (unit: J / g) Using a differential scanning calorimeter (DSC) (Hitachi High-Tech Science Corporation, DSC6220), 5 to 10 mg of a sample cut out from the resin composition pellet was heated from 30°C to 200°C at a constant heating rate of 10°C / min (1st heating) to melt the PLA crystals, and then held at 200°C for 5 minutes. Thereafter, the sample was cooled to 30°C at a constant heating rate of 10°C / min (1st cooling) and held for 5 minutes to recrystallize the PLA. The sample was again heated from 30°C to 200°C at a constant heating rate of 10°C / min (2nd heating) to melt the PLA crystals, and then held at 200°C for 5 minutes. It was then cooled to 30°C at a constant heating rate of 10°C / min (2nd cooling) and held for 5 minutes to recrystallize the PLA. The calorific value of PLA was calculated from the calorific value of PLA recrystallization at the 2nd cooling (which can be calculated from the peak area). In addition, the crystallinity of PLA was calculated using the value of 93 J / g (EW Fisher et al., Colloid-ZuZpoly., 251, 980 (1973)) as the melting enthalpy of infinite lamellar size of PLA. Table 5 shows the measurement results for Examples 6 and 7.

[0093] [Table 4]

[0094] [Table 5]

[0095] As shown in Table 4, it is found that Examples 1 to 10 have excellent rigidity (flexural modulus) and heat distortion temperature resistance. In addition, as shown by the fact that test pieces can be easily obtained by injection molding, the PLA resin composition of the present invention has a high crystallization rate and improved moldability. Furthermore, the obtained PLA resin composition not only has high rigidity and heat resistance, but also has excellent surface appearance (smoothness). Furthermore, the molded pieces have excellent dimensional stability (shrinkage rate, linear expansion coefficient, low warpage).

[0096] [Examples 11 to 18] The melt-kneading device was changed to a twin-screw extruder (Toshiba Machine Co., Ltd., product name "TEM37SS", L / D = 48), and the resin composition was continuously melt-kneaded (discharge: 20 kg / Hr) by quantitatively feeding the resin composition through a hopper provided at the most upstream position of the extruder using independent weight feeders. The cylinder temperature of the extruder was set to 200°C from the middle stage onwards. The rotation speed of the main screw of the twin-screw extruder was set to 100 rpm. The melt-kneaded resin composition was extruded in the form of strands, cooled in a water-cooled bath, and made into pellets with a length of about 3 mm. In Examples 11 to 16 and Example 18, the filler granules and polylactic acid shown in Table 6 were used in the amounts shown in Table 6. In addition, in Example 17, without using filler granules, 80 parts by weight of filler "B-1", 20 parts by weight of a 15 wt % aqueous solution of filler dispersion polymer "D-2", and 3 parts by weight of filler dispersant "C-1" were mixed at a rotation speed of 30 rpm for 6 minutes using a powder kneader "KDHJ-10", and the obtained powder mixture was fed into a twin-screw extruder to obtain a resin composition. In Example 17, since bridging occurred at the supply port during feeding of the powder mixture, the discharge rate was set to 10 kg / Hr to obtain pellets. The polylactic acid resin compositions obtained in Examples 11 to 18 were evaluated in the same manner as in Examples 1 to 10. The results are shown in Table 7.

[0097] [Table 6]

[0098] [Table 7]

[0099] As shown in Table 7, Examples 11 to 18 have excellent rigidity (flexural modulus) and heat distortion temperature resistance, excellent moldability, surface appearance (smoothness), and low warpage. Furthermore, the resin composition of the present invention can be preferably produced using a filler granule, but even if a powdery filler having a low bulk density is used, a PLA composition containing 30 to 70 parts by weight of a filler can be obtained with extremely high productivity. This is evident from the fact that in Example 17, the discharge rate is 10 kg / Hr, whereas in Example 14, which has a similar filler concentration, the resin composition can be stably refined at a discharge rate of 20 kg / Hr.

[0100] [Comparative Example 1] In Comparative Example 1, the results of measuring the physical properties of the polylactic acid resin composition not containing a filler are shown in Table 7.

[0101] [Reference example 1] 50 parts by weight of polylactic acid and 50 parts by weight of glass filler (GF; chopped strand, product name "ECS03T-187", manufactured by Nippon Electric Glass Co., Ltd.) were melt-kneaded in a twin-screw extruder (product name "TEM37SS", manufactured by Toshiba Machine Co., Ltd., L / D=48) to obtain a resin composition. Here, the GF was side-fed downstream of the extruder to obtain the composition. The evaluation results are shown in Table 7.

Claims

1. A polylactic acid resin composition comprising a polylactic acid resin and a filler, The polylactic acid resin composition further comprises a filler dispersant and / or a filler dispersing polymer, The filler is at least one selected from talc and mica, the filler dispersant is an ester compound having a hydrophobic group and a hydrophilic group, the filler dispersion polymer is at least one selected from the group consisting of polyethylene-based resins, polypropylene-based resins, polyvinyl alcohol-based resins, polystyrene-based resins, polyacrylate-based resins, polymethacrylate-based resins, and water-soluble polysaccharides; The content of the filler in the polylactic acid resin composition is 30% by weight to 70% by weight. The total content of the filler dispersant and the filler dispersion polymer in the polylactic acid resin composition is 0.1% by weight to 10% by weight, Form a molded product having a flexural modulus of 10 GPa or more at 23 ° C. Polylactic acid resin composition.

2. 2. The polylactic acid resin composition according to claim 1, wherein the filler dispersing agent is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, fatty acid amides, polyglycerin fatty acid esters, condensed hydroxy fatty acids, and alcohol esters of condensed hydroxy fatty acids.

3. 3. The polylactic acid resin composition according to claim 1, wherein the filler dispersion polymer is a polyvinyl alcohol resin.

4. The method includes melt-kneading a polylactic acid resin and a filler granule, The filler granules contain the filler and the filler dispersant and / or the filler dispersion polymer, The filler is at least one selected from talc and mica, the filler dispersant is an ester compound having a hydrophobic group and a hydrophilic group, the filler dispersion polymer is at least one selected from the group consisting of polyethylene-based resins, polypropylene-based resins, polyvinyl alcohol-based resins, polystyrene-based resins, polyacrylate-based resins, polymethacrylate-based resins, and water-soluble polysaccharides; The content of the filler in the filler granules is 80 parts by weight to 99.9 parts by weight based on 100 parts by weight of the filler granules. A method for producing a polylactic acid resin composition.

5. A molded article formed from the polylactic acid resin composition according to any one of claims 1 to 3, A molded body having a flexural modulus at 23°C of 10 GPa or more.

6. A molded article formed from the polylactic acid resin composition according to any one of claims 1 to 3, A molded body having a deflection temperature under load of 120°C or higher under a load of 0.45 MPa.

7. An injection-molded article formed from the polylactic acid resin composition according to any one of claims 1 to 3.

8. An extrusion molded article formed from the polylactic acid resin composition according to any one of claims 1 to 3.

9. A sheet-like shaped product formed from the polylactic acid resin composition according to any one of claims 1 to 3.

10. A 3D printer model formed from the polylactic acid resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Polylactic acid-based resin composition and method for producing the same

    JP2004352844A

  • Biodegradable resin composition

    JP2007131690A

  • Wood fiber pellet manufacturing method

    JP2009508708A